New insights into combined surfzone, embayment, and estuarine bathing hazards - C. Stokes; T. Poate; G. Masselink; T. Scott; S. Instance (Natural Hazards and Earth System Sciences)
Rip currents are the single largest cause of beach safety incidents globally, but where an estuary mouth intersects a beach, additional flows are created that can exceed the speed of a typical rip current, significantly increasing the hazard level for bathers. However, there is a paucity of observations of surfzone currents at estuary mouth beaches, and our understanding and ability to predict how the bathing hazard varies under different wave and tide conditions are therefore limited. Using field observations and process-based XBeach modelling at an embayed, estuary mouth beach, we demonstrate how surfzone currents can be driven by combinations of estuary discharge and wave-driven bathymetric and boundary rip currents under various combinations of wave and tide forcing. While previous studies have demonstrated the high hazard that rip currents pose, typically during lower stages of the tide, here we demonstrate that an estuary mouth beach can exhibit flows reaching 1.5 m s−1 – up to 50 % stronger than typical rip current flows – with a high proportion (> 60 %) of simulated bathers exiting the surfzone during the upper half of the tidal cycle. The three-dimensional ebb shoal delta was found to strongly control surfzone currents by (1) providing a conduit for estuary flows that connect to headland boundary rips and (2) acting as a nearshore bar system to generate wave-driven “river channel bathymetric rips”. Despite significant spatio-temporal variability in the position of the river channels on the beach face, it was possible to hindcast the timing and severity of past bathing incidents from model simulations, providing a means to forewarn bathers of hazardous flows.